Government's advertising information content strategy in newspaper print advertisement / Mardzuki Mazlan, Mohd Sazili Shahibi and Wan Ab. Kadir Wan Dollah - Mazlan, Mardzuki; Shahibi, Mohd Sazili; Wan Dollah, Wan Ab. Kadir (Universiti Teknologi MARA, Selangor, 2020)
In advertising, one of the important and critical part is dissemination of information through communication. Communication is about transmitting, receiving, and processing information between two parties. Therefore, information content of the advertisement is important to ensure the effectiveness of communication through advertising. This research's focus is towards finding and discussing information content strategy towards effective advertising. It will explore the strategy in disseminating effective content through print advertising especially in promoting government policies and initiatives by examining the factors related to the effectiveness. The internet and online has emerge to be one of the important medium for advertising, with the popularity of social media, it is no question the high expenditure of digital advertising compared to print advertising. However, print advertising is still considered an important medium by the advertiser. One way that is often used by the government is the use of advertising as a medium of communication in transferring information to the public, to create awareness and educate public on certain issues through a series of campaign. The government must response with the constant changing of the demands of the public's preferences to improve efficiency. The respondent involved was postgraduate students of research universities in Malaysia and newspaper advertisement is the main medium in this research. In this paper, it discussed the findings in factors related to the effectiveness of advertising information and to propose the improvement of government communication. Lastly, the researcher highlights the implications of this research to the society and future directions for future research